Cro-Magnon how the Ice Age gave birth to the first modern humans - Fagan, Brian M (Bloomsbury Press, 2010)
Cro-Magnons were the first fully modern Europeans--not only the creators of the stunning cave paintings at Lascaux and elsewhere, but the most adaptable and technologically inventive people that had yet lived on earth. The prolonged encounter between the Cro-Magnons and the archaic Neanderthals, between 45,000 and 30,000 years ago, was one of the defining moments of history. The Neanderthals survived for some 15,000 years in the face of the newcomers, but were finally pushed aside by the Cro-Magnons' vastly superior intellectual abilities and cutting-edge technologies. What do we know about this remarkable takeover? Who were these first modern Europeans and what were they like? How did they manage to thrive in such an extreme environment? And what legacy did they leave behind them after the cold millennia? This is the story of a little known, yet seminal, chapter of human experience.